Level of Physical Activity in Adolescents who Attend Secondary School in Lima Institute - Richart Gabriel López Salazar; Carlos David Neyra Rivera; Ericson Gutiérrez Ingunza (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: the lack of physical activity is linked to high levels of sedentary behavior, which constitutes an important risk factor for the development of chronic diseases such as: overweight and obesity, which in adolescents has become a health problem worldwide. Objective: to determine the level of physical activity of the students of the secondary level of a public school in Lima. Method: a descriptive and cross-sectional study was carried out in which students between the ages of 12 and 17 enrolled in the 2019 school year were included. The population consisted of 470 high school students from the Institución Educativa Simón Bolívar school in the Palomino Urbanization of Cercado de Lima. The Inventory of Habitual Physical Activity for Adolescents and the eating behaviors module of the World Health Survey of Schoolchildren were applied. Simple random probabilistic sampling was used. Results: 52.3 % of the patients were male, the most frequent age range was 13 to 15 years with 70.1 %. Most presented a normal nutritional status (83.3 %). The level of habitual physical activity was mostly moderate with 62 % followed by low with 19.5 % and high with 18.3 %. Conclusions: the level of total habitual physical activity presented by the students of this educational institution is moderate, which does not meet the recommended levels of physical activity for children and adolescents.